Abdominal cocoon - Manohar, Aishwarya Emerald; Sabarigirieasen, M.; Nedunchezhian, S.; Kannan, R. (International Surgery Journal, 2021)
Cocoon abdomen is relatively a rare entity that is encountered less often during our surgical practice and is usually seen in young females. We present two cases of abdominal cocoon in middle age and elderly males both having different clinical presentations and management. Firstly, we had a 34 years male was admitted with complaints of diffuse abdominal pain and obstipation for 3 days. Abdomen was grossly distended with sluggish bowel sounds and computed tomography (CT) was suggestive of dilated small bowel loops. Laparotomy revealed a thin peritoneal covering encapsulating the small bowel loops and a band arising from the right parietal wall to the ileum. Band release and adhesiolysis was performed. He had an uneventful post-operative recovery and is on follow up now. Our second patient was a 60 years male, who presented with diffuse abdominal pain and distension for 2 weeks and vomiting for 4 days. There was abdominal distension, visible intestinal persistalsis, fullness of the flanks, exaggerated bowel sounds and a irreducible right inguinal hernia. CT revealed obstructed right inguinal hernia with large bowel as content. The right inguinal region was explored and a thick shiny membrane was found covering the contents of the sac. After adhesiolysis and herniorraphy, patient initially recovered well, but later succumbed due to medical causes unrelated to surgery. It is clear that both these cases represent two distinct clinical spectrum of a similar pathological process which has to be considered as one of the differential diagnoses in patients with equivocal clinical findings.